Long-Term Effect of Group Support Psychotherapy on Depression and HIV Treatment Outcomes: Secondary Analysis of a Cluster Randomized Trial in Uganda. Issue 8 (6th October 2022) - Nakimuli-Mpungu, Etheldreda; Smith, Colin M.; Wamala, Kizito; Okello, James; Birungi, Josephine; Etukoit, Micheal; Mojtabai, Ramin; Nachega, Jean B.; Harari, Ofir; Musisi, Seggane; Mills, Edward J.
ABSTRACT: Objective: We aimed to determine the effect of group support psychotherapy (GSP) compared with group HIV education (GHE) on depression and HIV treatment outcomes 24 months after treatment. We further aimed to investigate the mediating role of depression and antiretroviral therapy (ART) adherence in the relationship between GSP and viral load suppression. Methods: Thirty HIV clinics across three districts were randomly assigned to deliver either GSP or GHE for depression. Depression and optimal (≥95%) ART adherence was assessed at baseline and 6, 12, 18, and 24 months after treatment. Viral load was drawn from the medical charts at baseline and 12 and 24 months after treatment. Multilevel mixed-effects regression models and generalized structural equation modeling were used to estimate 24-month outcomes and mediation effects. Results: Participants ( N = 1140) were enrolled from HIV clinics offering either GSP ( n = 578 [51%]) or GHE ( n = 562 [49%]). Fewer GSP than GHE participants met the criteria for depression at 24 months after treatment (1% versus 25%; adjusted odds ratio [aOR] = 0.002, 95% confidence interval [CI] = 0.0002–0.018). More GSP than GHE participants reported optimal (≥95%) ART adherence (96% versus 88%; aOR = 20.88, 95% CI = 5.78–75.33) and improved viral suppression (96% versus 88%; aOR = 3.38, 95% CI = 1.02–11.02). The indirect effects of GSP through sequential reduction in depression and improvement in ART adherence at 12 months may partially explain the higher viral suppression rates at 24 months in GSP than GHE groups. Conclusion: In settings where the HIV epidemic persists, depression treatment with GSP may be critical for optimal HIV treatment outcomes. Trial Registration: The Pan African Clinical Trials Registry, number PACTR201608001738234.